Study on blood condition of Helostoma temmincki from the flood water swamp Tapung River and the Sail River, Riau Province - Sari, Yolla Novita; Putra, Ridwan Manda; ', Windarti (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
Helostoma temmincki is a freshwater omnivorous fish and it can be found in theTapung River swamp and in the Sail River. The water quality in the Tapung River swampis relatively good condition, while the water quality in the Sail River is bad it is polluted.As the water quality in general affects the blood condition of the fish, it is predicted thatblood condition of H. temmincki from the Tapung River swamp and the Sail Riverdifferent. To understand blood condition of H. temmincki from both areas, this study hasbeen conducted from February to March 2015. There are 9 fishes from the Tapung Riverswamp and 9 fishes from the Sail River. The fish blood was taken and analyzed forerythrocytes and leukocytes content, hematocrite and leucocrite levels and types ofleukocytes present. Results shown that the erythrocytes of fish from the Tapung Riverswamp was 2,658,889 cells/mm3 and that of the Sail River was 2,318,889 cells/mm3. Thenumber of the leukocytes of the Tapung River swamp fish was 176,389 cells/mm3 and thatof the Sail River fish was 200,056 cells/mm3. There were 5 types of white blood cells inH.temmincki, namely lymphocytes, thrombocytes, monocytes, basophiles, and neutrophils.Based on data obtained it can be concluded that the blood condition of H. temmincki fromthe Tapung River swamp was better than that of the Sail River.Key words: Tapung River swamp, Sail River, Helostoma temmincki, blood